Grain Refinement and Improved Mechanical Properties of EUROFER97 by Thermo-Mechanical Treatments - Giulia Stornelli; Andrea Di Schino; Silvia Mancini; Roberto Montanari; Claudio Testani; Alessandra Varone (Applied Sciences, 2021)
EUROFER97 steel plates for nuclear fusion applications are usually manufactured by hot rolling and subsequent heat treatments: (1) austenitization at 980 °C for 30 min, (2) rapid cooling and (3) tempering at 760 °C for 90 min. An extended experimental campaign was carried out with the scope of improving the strength of the steel without a loss of ductility. Forty groups of samples were prepared by combining cold rolling with five cold reduction ratios (20, 40, 50, 60 and 80%) and heat treatments at eight different temperatures in the range 400–750 °C (steps of 50 °C). This work reports preliminary results regarding the microstructure and mechanical properties of all the cold-rolled samples and the effects of heat treatments on the samples deformed with the greater CR ratio (80%). The strength of deformed samples decreased as heat treatment temperature increased and the change was more pronounced in the samples cold-rolled with greater CR ratios. After heat treatments at temperature up to 600 °C yield stress (YS) and ultimate tensile strength (UTS) of samples deformed with CR ratio of 80% were significantly larger than those of standard EUROFER97 but ductility was lower. On the contrary, the treatment at 650 °C produced a fully recrystallized structure with sub-micrometric grains which guarantees higher strength and comparable ductility. The work demonstrated that EUROFER97 steel can be strengthened without compromising its ductility; the most effective process parameters will be identified by completing the analyses on all the prepared samples.